Quality Of Patient Care Among ICU Nurses During Prolonged Health Crises And Extended Length Of Stay (LOS) (The Review of Diabetic Studies, 2025)
Background: Quality of patient care in Intensive Care Units (ICUs) is critical to patient outcomes, yet it faces significant challenges during prolonged health crises and extended patient length of stay (LOS). These conditions exacerbate stressors such as high workload, staff shortages, and psychological fatigue among nurses, potentially compromising care standards. This study aimed to assess the quality of patient care as perceived by ICU nurses during such demanding periods.Methods: A descriptive cross-sectional study was conducted across several tertiary hospitals. A sample of 198 ICU nurses was selected using stratified random sampling. Data were collected using a validated, self-administered questionnaire that assessed demographic and workload variables, the impact of the crisis, and perceptions of care quality across five dimensions: timeliness, safety, communication, compassion, and adherence to protocols. Data were analyzed using SPSS version 27.0, employing descriptive statistics and inferential tests like Chi-square and ANOVA.Results: The majority of nurses reported increased stress (86.9%), staff shortages (82.8%), and inadequate resources (68.7%). Overall, the perceived quality of care was high (mean score: 3.98/5). The highest-rated dimensions were adherence to protocols (71.7% high quality) and patient safety practices (69.7% high quality). In contrast, communication (58.6% high quality) and timeliness of care (61.6% high quality) scored lower. A statistically significant relationship (p=0.003) was found between years of experience and perceived care quality, with nurses having more than six years of experience reporting higher quality care (83.8%) compared to those with less than three years (43.5%).Conclusion: ICU nurses maintained high standards of procedural and safety-focused care during prolonged crises, demonstrating strong professional commitment. However, interpersonal and timely aspects of care were more vulnerable to the effects of workload and fatigue. The findings underscore the need for healthcare institutions to strengthen institutional support, address staffing shortages, and protect nurses' well-being to sustain all dimensions of high-quality, patient-centered care in future extended health crises.